Understanding craniosynostosis as a growth disorder. (22nd March 2016) - Flaherty, Kevin; Singh, Nandini; Richtsmeier, Joan T.
Abstract : Craniosynostosis is a condition of complex etiology that always involves the premature fusion of one or multiple cranial sutures and includes various anomalies of the soft and hard tissues of the head. Steady progress in the field has resulted in identifying gene mutations that recurrently cause craniosynostosis. There are now scores of mutations on many genes causally related to craniosynostosis syndromes, though the genetic basis for the majority of nonsyndromic cases is unknown. Identification of these genetic mutations has allowed significant progress in understanding the intrinsic properties of cranial sutures, including mechanisms responsible for normal suture patency and for pathogenesis of premature suture closure. An understanding of morphogenesis of cranial vault sutures is critical to understanding the pathophysiology of craniosynostosis conditions, but the field is now poised to recognize the repeated changes in additional skeletal and soft tissues of the head that typically accompany premature suture closure. We review the research that has brought an understanding of premature suture closure within our reach. We then enumerate the less well‐studied, but equally challenging, nonsutural phenotypes of craniosynostosis conditions that are well characterized in available mouse models. We consider craniosynostosis as a complex growth disorder of multiple tissues of the developing head, whose growth is also targeted by identified mutations in ways that are poorly understood. Knowledge gained from studies of humans and mouse models for these conditions underscores the diverse, associated developmental anomalies of the head that contribute to the complex phenotypes of craniosynostosis conditions presenting novel challenges for future research. WIREs Dev Biol 2016, 5:429–459. doi: 10.1002/wdev.227 This article is categorized under: Birth Defects > Craniofacial and Nervous System Anomalies